PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA TOKO RITEL - Komalasari, Monica; FCW Sutrisno, Timotius; Endi Sarwoko, (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study aims to analyze the influence of leadership style, motivation, and work environment on employee performance in Marlin Group retail stores. The research involved 97 respondents from various Marlin Group branches using a quantitative survey method. Data analysis was conducted using the Partial Least Square (PLS) approach to test the validity, reliability, and significance of relationships between variables. The results showed that only the motivation variable had a significant and positive effect on employee performance. In contrast, leadership style and work environment did not have a significant impact. These findings highlight the importance of enhancing work motivation systems, both intrinsic and extrinsic, as a key strategy to boost employee productivity and performance. This study also offers practical implications for retail store management in developing more effective human resource policies. Keywords: Leadership Style, Motivation, Work Environment, Employee Performance, Retail Store